The Atlantic flight; The trans-atlantic flight; Newfoundland to the Azores
Three picture essays on transatlantic flights. The first two are about Mackenzie-Grieve and Hawker's failed flight from Newfoundland to Ireland in May 1919. The third is about the successful American flying boat trip from Newfoundland to the Azores by Lieutenant-Commander Read that same month. Periodical covers have been included with many of the digitized articles whether they relate to them or not. Extra pages not part of the article in question may also be present.